The Existence of Equilibrium Flows - Alfred Galichon; Larry Samuelson; Lucas Vernet (Journal of Mechanism and Institution Design)

(untitled)
In this paper, we establish conditions for the existence of an equilibrium in the equilibrium flow problem studied by Galichon et al. (2024). The problem nests several classical economic models such as bipartite matching models, hedonic pricing models, shortest-path and minimum-cost flow problems, and time-dependent routing problems.